The Swordbearers : Studies in Supreme Command in the First World War - Barnett, Correlli (London Eyre & Spottiswoode, 1963)
Four of the most important World War I commanders-in-chief helped determine its outcome--and, by extension, the course of the 20th century. Here are the stories of Colonel-General von Molke, who attempted to defeat France in a mere 6 weeks; Admiral Sir John Jellicoe, who struggled unsuccessfully to crush the German High Sea Fleet; General Pétain, whose inaction led the French troops to mutiny; and General Ludendorff, who mounted a titanic German offensive...that failed.
Include Illustrations, Maps, Appendix, Bibliography and Index.
Studies in Supreme Command in the First World War.
Keywords: Military campaigns -- World War (1914-1918)